2019
DOI: 10.1002/art.40900
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde–Acetaldehyde Adducts and Antibody Responses in Rheumatoid Arthritis–Associated Interstitial Lung Disease

Abstract: Objective To compare serum anti–malondialdehyde–acetaldehyde (anti‐MAA) antibody levels and MAA expression in lung tissue from patients with rheumatoid arthritis–associated interstitial lung disease (RA‐ILD) to those found in controls. Methods Anti‐MAA antibody (IgA, IgM, IgG) concentrations were measured in patients with RA‐ILD and compared to those of RA patients with chronic obstructive pulmonary disease (COPD) and RA patients without lung disease. Associations between anti‐MAA antibody with RA‐ILD were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Various novel candidates have been proposed for RA-ILD screening, including imaging techniques such as positron emission tomography and pulmonary ultrasound,22 23 or serum biomarkers such as the matrix metalloproteinases 7, surfactant protein D and Krebsvon del Lungen-6 4 5. RA-ILD has been associated with different antimodified protein antibodies (AMPAs) based on citrulline24 25 and more recently, malondialdehyde–acetaldehyde adducts 26. Screening techniques can increase RA-ILD diagnostic accuracy, although a model based on features used in clinical practice such as age, sex, smoking, RF and ACPA has a potent screening capacity for symptomatic and subclinical RA-ILD 4.…”
Section: Discussionmentioning
confidence: 99%
“…Various novel candidates have been proposed for RA-ILD screening, including imaging techniques such as positron emission tomography and pulmonary ultrasound,22 23 or serum biomarkers such as the matrix metalloproteinases 7, surfactant protein D and Krebsvon del Lungen-6 4 5. RA-ILD has been associated with different antimodified protein antibodies (AMPAs) based on citrulline24 25 and more recently, malondialdehyde–acetaldehyde adducts 26. Screening techniques can increase RA-ILD diagnostic accuracy, although a model based on features used in clinical practice such as age, sex, smoking, RF and ACPA has a potent screening capacity for symptomatic and subclinical RA-ILD 4.…”
Section: Discussionmentioning
confidence: 99%
“…79 MAA (the antigen) can also be found in higher concentrations in lung tissue of RA patients with interstitial lung disease (ILD) as compared to ILD patients without RA. 80 Unlike AAPA and anti-CarP, anti-MAA were not shown to be cross-reactive with ACPA (discussed below), which could indicate that this response is less related to the other AMPA ( Figure 3). 79 Anti-MAA antibodies have furthermore been reported in patients with osteoarthritis, systemic lupus erythematosus, and even alcohol use disorders, indicating that they lack RA specificity.…”
Section: Anti -Ma a And Anti -Mda Antibod Ie Smentioning
confidence: 99%
“…Anti‐MAA antibodies are associated with coronary artery disease and are furthermore found in RA patients, mainly but not exclusively within the seropositive group . MAA (the antigen) can also be found in higher concentrations in lung tissue of RA patients with interstitial lung disease (ILD) as compared to ILD patients without RA . Unlike AAPA and anti‐CarP, anti‐MAA were not shown to be cross‐reactive with ACPA (discussed below), which could indicate that this response is less related to the other AMPA (Figure ) .…”
Section: Anti‐maa and Anti‐mda Antibodiesmentioning
confidence: 99%
“…Several studies have also identified male sex as a risk factor for RA‐ILD, including Bongartz and colleagues who reported that the risk of RA‐ILD was 4.4‐fold higher in men vs women . In addition, there is growing evidence associating RA, ILD, and the presence of multiple autoantibodies, including RF, ACPA, and other autoantibody systems including antibodies to heat‐shock protein‐90 (anti‐HSP90), malondialdehyde‐acetaldehyde adducts (anti‐MAA), and anti‐PAD antibodies …”
Section: Risk Factors For Ra‐related Lung Diseasementioning
confidence: 99%
“…Several studies have also identified male sex as a risk factor for RA-ILD, including Bongartz and colleagues who reported that the risk of RA-ILD was 4.4-fold higher in men vs women. 48 In addition, there is growing evidence associating RA, ILD, and the presence of multiple autoantibodies, including RF, ACPA, and other autoantibody systems including antibodies to heat-shock protein-90 (anti-HSP90), 49,50 malondialdehyde-acetaldehyde adducts (anti-MAA), 51 and anti-PAD antibodies. 52 While several studies have suggested a relationship between the genetic factor the shared epitope and ILD in RA, 36 that relationship may be confounded by other associations between the shared epitope, smoking (another risk factor for lung disease), and autoantibody positivity in RA.…”
Section: Risk Factors For Ild In Ramentioning
confidence: 99%